Pengembangan Aplikasi Pembelajaran dengan Menerapkan Model Pembelajaran Teams-Games-Tournament (TGT) - Anita Rizky Agustina; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2021)
UPT SMP Negeri 6 Gresik is one of the few educational institutions that implement a Teams-Games-Tournament (TGT) learning model in their day-to-day class learning activities. The TGT learning model can assist students in understanding the learning materials by relying on their friends as age-equivalent tutors and via game elements. The current model that was being applied has several issues, where teachers formed the groups conventionally which could decrease the in-class study time. Conventional ways of forming a group leave room for an unfair knowledge distribution among groups, such as a group having only students who have high grades or low grades only. Other than that, the teachers will make a crossword puzzle conventionally. The playing board is made before a learning material is given to the students and the amount of “words” on the puzzle are determined on much material there is and how many groups are formed. The grouping feature is developed using k-means clustering. The development process used the waterfall development process and Codeigniter framework. This application requirement analysis resulted in four actors, 37 functional requirements, and one non-functional requirement. Testing for this research was done by blackbox testing techniques and whitebox testing techniques.